2011
DOI: 10.1007/s11195-011-9234-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Scale for Body and Sexual Self-Esteem in Athletes with Disabilities

Abstract: The objective was to examine the sexual and body self-esteem of Brazilian competitive athletes with physical disabilities using The Physical Disability Sexual and Body Esteem Scale (PDSBE). This study involved 150 men and 58 women over 18 years of age engaged in various sports activities. The participants obtained a mean of 42.66 (±8.11) on the scale for body and sexual self-esteem. Mean scores were similar for both sexes and among types of physical disability. The body and sexual self-esteem indexes for Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In the original version, questions were loaded in 3 factors; sexual esteem, body esteem, and attractiveness to others [28] . Our results are similar to a study conducted in Brazil, suggesting that for Iranian women like Brazilian women, others' opinions may be more important in self-evaluation of body esteem [13] . In a study carried out by Lease, Cohen, and Dahlbeskin, a different cultural setting, it has been reported that for people with physical disability, body esteem is strongly associated with social environment [30] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the original version, questions were loaded in 3 factors; sexual esteem, body esteem, and attractiveness to others [28] . Our results are similar to a study conducted in Brazil, suggesting that for Iranian women like Brazilian women, others' opinions may be more important in self-evaluation of body esteem [13] . In a study carried out by Lease, Cohen, and Dahlbeskin, a different cultural setting, it has been reported that for people with physical disability, body esteem is strongly associated with social environment [30] .…”
Section: Discussionsupporting
confidence: 89%
“…Exploratory and confirmatory factor analysis using varimax rotation showed 3 factors namely sexual esteem, attractiveness to others, and body esteem. However, factor analysis by Ferando et al extracted only 2 factors (sexual esteem and sexual attractiveness) [13] . At present, there is no gold standard for the longterm treatment of women with PCOS, who do not want to get pregnant.…”
Section: Introductionmentioning
confidence: 99%
“…Human sexuality is a complex issue that as well as being an important aspect of our functioning is also a scientific discipline encompassing the psychology of emotional and motivational processes, and part of the model approximating the regulation of human functioning. The self-image of one’s sex life (sexual esteem) and sexual needs that all people develop guide their actions in this intimate sphere of life [7, 12, 61, 62, 66, 72]. However, sexual esteem and sexual needs are not the only factors that influence sexual activity manifested through specific sexual behaviors [21, 26, 49]: their range includes also body performance and especially the level of physical fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with people without SCI showed higher scores of resilience in athletes when compared with sedentary individuals (12)(13)(14)(15). Sport has the ability to enhance athletic identity and self-esteem, so that individuals who practice sport develop the confidence to face and deal with their deficiencies (12)(13)(14)(15). However, we found no studies that evaluated the relationship between resilience and sexual adjustment in males with SCI.…”
Section: Discussionmentioning
confidence: 82%
“…The questionnaire on physical and sexual esteem was developed by Taleporos & McCabe (12) and validated in Brazil for people with physical disabilities (13). The respondents answer 10 questions on a 5-point Likert scale (1 = strongly agree to 5 = strongly disagree), based on the convention that higher values on the scale denote higher body and sexual self-esteem.…”
Section: Instrumentsmentioning
confidence: 99%